Manganese-Enhanced Magnetic Resonance Imaging and Studies of Rat Behavior: Transient Motor Deficit in Skilled Reaching, Rears, and Activity in Rats After a Single Dose of MnCl2. (2nd May 2017) - Alaverdashvili, Mariam; Lapointe, Valerie; Whishaw, Ian Q; Cross, Albert R
Manganese-enhanced magnetic resonance imaging (MEMRI) has been suggested to be a useful tool to visualize and map behavior-relevant neural populations at large scale in freely behaving rodents. A primary concern in MEMRI applications is Mn 2+ toxicity. Although a few studies have specifically examined toxicity on gross motor behavior, Mn 2+ toxicity on skilled motor behavior was not explored. Thus, the objective of this study was to combine manganese as a functional contrast agent with comprehensive behavior evaluation. We evaluated Mn 2+ effect on skilled reach-to-eat action, locomotion, and balance using a single pellet reaching task, activity cage, and cylinder test, respectively. The tests used are sensitive to the pathophysiology of many neurological and neurodegenerative disorders of the motor system. The behavioral testing was done in combination with a moderate dose of manganese. Behavior was studied before and after a single, intravenous infusion of MnCl2 (48 mg/kg). The rats were imaged at 1, 3, 5, 7, and 14 days following infusion. The results show that MnCl2 infusion resulted in detectable abnormalities in skilled reaching, locomotion, and balance that recovered within 3 days compared with the infusion of saline. Because some tests and behavioral measures could not detect motor abnormalities of skilled movements, comprehensive evaluation of motor behavior is critical in assessing the effects of MnCl2 . The relaxation mapping results suggest that the transport of Mn 2+ into the brain is through the choroid plexus-cerebrospinal fluid system with the primary entry point and highest relaxation rates found in the pituitary gland. Relaxation rates in the pituitary gland correlated with measures of motor skill, suggesting that altered motor ability is related to the level of Mn circulating in the brain. Thus, combined MEMRI and behavioral studies that both achieve adequate image enhancement and are also free of motor skills deficits are difficult to achieve using a single systemic dose of MnCl2 .